Analysis of Sharia Banking Stock Returns in Indonesia in 2021-2024 - Daradinanti, Reny Widia; Harris, Helmi (Universitas Muhammadiyah Surakarta, 2024)
This study aims to analyze whether Return On Asset, Return On Equity, and Net Profit Margin have a significant influence on Stock Returns. This research was conducted using the object of Islamic banking companies listed on the Indonesia Stock Exchange for the 2021-2024 period. The method used in this analysis is multiple linear regression with the help of E-views software 13. The tests include model selection tests, classical assumption tests, and multiple linear regression tests. Sampling was carried out using a saturated sampling technique with a sample of 4 Islamic banking companies listed on the Indonesia Stock Exchange, namely Bank Syariah Indonesia Tbk, Bank Tabungan Pensiunan Negara Tbk, Bank Panin Dubai Syariah Tbk, and Bank Aladin Syariah Tbk. Data is obtained from the monthly reports of each company for the 2021-2024 period, and stock return data is taken from the closing stock price every month. Based on the feasibility test, ROA, ROE, and NPM simultaneously do not affect Stock Returns. Then, based on the t-test analysis, it was stated that ROA significantly affected Stock Returns. In contrast, ROE and NPM did not significantly affect Stock Returns in Islamic banking companies listed on the Indonesia Stock Exchange for the 2021-2024 period.